2016
DOI: 10.1016/j.eurpsy.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking status and MADRS retardation factor on response to low frequency repetitive transcranial magnetic stimulation for depression

Abstract: Low MADRS retardation factor and ex-smoker status is highly prevalent in responders to low frequency rTMS. Further studies are needed to investigate the predictive value of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Early prediction of trajectory of response is of main interest to avoid false hope in patients and to decrease the financial and time burden associated with rTMS treatment in patients with MDE. Some clinical (e.g., retardation, smoking status [4]) and biological measures such as neurophysiological features (e.g., cortical excitability measures), genetic polymorphisms (e.g., BDNF or COMT) and imaging measures (with either EEG, PET, SPECT or fMRI) have been proposed as predictive markers of response to rTMS [5]. However, their large-scale use in clinical settings is limited by their usefulness at an individual level as well as their costs and accessibility.…”
Section: Dear Editormentioning
confidence: 99%
“…Early prediction of trajectory of response is of main interest to avoid false hope in patients and to decrease the financial and time burden associated with rTMS treatment in patients with MDE. Some clinical (e.g., retardation, smoking status [4]) and biological measures such as neurophysiological features (e.g., cortical excitability measures), genetic polymorphisms (e.g., BDNF or COMT) and imaging measures (with either EEG, PET, SPECT or fMRI) have been proposed as predictive markers of response to rTMS [5]. However, their large-scale use in clinical settings is limited by their usefulness at an individual level as well as their costs and accessibility.…”
Section: Dear Editormentioning
confidence: 99%
“…Other analyses may support certain conclusions-although still highly debated in the literature-on the basis of the 3-factor model of the MADRS, mainly used to assess clinical features of (non)responders to neurostimulation treatments. 73,74 The "dysphoria" factor 1 (including reported sadness, pessimistic thoughts, and suicidal thoughts) and the "retardation" factor 2 (including apparent sadness, concentration difficulties, lassitude, and inability to feel) showed notable improvement from the first week (−26.7% and −20%, respectively; P < 0.001), with the most positive changes in reported sadness, apparent sadness, and lassitude.…”
Section: Discussionmentioning
confidence: 99%
“…141 Moreover, greater response to a LF-rTMS protocol has been associated with lower MADRS retardation scores at baseline. 142 Regarding ECT, even first-line recommendations such as older age, psychosis, and melancholic features 21 were not consistently identified in a meta-analysis. 133 One study reported that ECT responders displayed higher scores on a MADRS dysphoria factor compared to nonresponders, while the procedure had only a small effect on a MADRS vegetative factor.…”
Section: Convulsive Modalitiesmentioning
confidence: 98%